Online hate and harmful content : cross-national perspectives - Keipi, Teo 1984- (Routledge advances in sociology, 2017)
Evolving social media -- Social media and identity -- Lifestyle and online risks -- The rise of online hate -- Impacts of online hate -- Harm-advocating content online -- Social spheres of online hate -- Transformation of social networks and interactions